An impedance-match design scheme for inductively active power filter in distribution networks. (July 2018) - Yu, Jiaqi; Li, Yong; Cao, Yijia; Xu, Yong
Highlights: This article proposes an IAPF to compensate harmonics from nonlinear loads. Influences on compensation accuracy, perturbation rejection ability are analyzed. The IAPF can prevent wide-bandwidth harmonics from flowing into the primary side. Abstract: This article proposes an improved inductively active power filter (IAPF) to compensate the wide-bandwidth harmonics from nonlinear loads and eliminate the switching harmonics' adverse effect for its own inverter. At first, the topology that consists of an inductively filtering converter transformer (IFCT) and a shunt active power filter (SAPF) is proposed. The system equivalent circuit, including fundamental and harmonic impedances of IFCT and SAPF, is established to reveal the filtering mechanism. Besides, the mathematical model, control strategy and detailed output impedance of SAPF are described, respectively. Further, according to the equivalent circuit, comprehensive influences of IFCT equivalent impedance and SAPF out impedance on system compensation accuracy, perturbation rejection ability and stability are theoretically analyzed, the impedance-match operation constraints between two impedances are revealed. By proper IFCT design, a simple but practical method to reduce the interaction between IFCT and SAPF is proposed. Comparative simulation cases in 10 kV distribution networks and the proper experiment in 380 V condition are performed. The corresponding results validate the effectiveness and correctness of the proposed IAPF.